Impacts of Mootral on Methane Production, Rumen Fermentation, and Microbial Community in an in vitro Study - Ahmed, Eslam; Yano, Rintaro; Fujimori, Miho; Kand, Deepashree; Hanada, Masaaki; Nishida, Takehiro; Fukuma, Naoki (Frontiers in Veterinary Science, 2021)
Methane mitigation strategies have a two-side benefit for both environment and efficient livestock production. This preliminary short-term in vitro trial using Mootral (garlic and citrus extracts), a novel natural feed supplement, was conducted to evaluate its efficacy on rumen fermentation characteristics, methane production, bacterial and archaeal community. The experiment performed as a batch culture using rumen fluid collected from sheep, and Mootral was supplemented in three concentrations; 0 (Control), 10, and 20% of the substrate (50% Grass: 50% Concentrate). After the incubation for 24 hours at 39oC, Mootral in a dose-dependent manner improved the production of total volatile fatty acids and propionate while reduced the acetate proportion and acetate/propionate ratio. The total produced gas was two-times more in Mootral supplemented groups than control, while the proportion of methane in the produced gas reduced by 22 and 54% for 10 and 20% Mootral, respectively. Mootral did not change pH, digestibility, and ammonia-nitrogen. Microbial community analyses showed that Mootral effectively changed the ruminal microbiome. The bacterial community showed increase of the relative abundance of propionate-producing family such as Prevotellaceae and Veillonellaceae, while there was a decrease in the relative abundance of some hydrogen producing bacteria by Mootral supplementation. In the archaeal community, Methanobacteriaceae was decreased by Mootral supplementation comparing with control, while the Methanomassiliicoccaceae family increased in a dose-dependent effect. The results of the study showed the efficacy of the new mixture to alter the ruminal microbial community, produce more propionate and reduce microbial groups associated with methane production, thus suggesting that Mootral is a promising natural mixture for methane reduction from ruminants.